Transmission characteristics of train-induced vibration in buildings based on wave propagation analysis. (16th May 2023) - Cao, Rongning; Ma, Meng; Sun, Xiaojing; Chen, Jialiang
Highlights: A single-span periodic structure model was developed using wave propagation analysis. An abstract model of the multi-span periodic structure was developed from the perspective of wave propagation. Residential frame buildings typically contain two main vertical vibration modes below 100 Hz. The total vibration transmission characteristics are related to the mode shape and vibration mode participation. Abstract: Various studies have focused on predicting, evaluating, and controlling train-induced building vibrations and radiated noise. This study aimed to clarify the theory of building vibration transmission by investigating the transmission characteristics of vibrations in buildings using wave propagation analysis. First, the building was modelled as a periodic structure, as each floor was similar in layout. Based on the wave propagation method, a periodic structure model was established in which the dynamic stiffness matrix of the cell structure could be derived using the spectral element method. Second, a response transfer function (RTF) database of 140 simplified typical residential buildings was established by wave analysis method. Finally, the transmission laws of train-induced vibration were studied. The results indicated that the vibration transmission laws were related to the mode shapes of structures and the participation of modes, which was affected by the spectral characteristics of the input excitation. With an increase in building height, the natural frequency decreased, which influenced the participation of each mode, and this would cause the transmission characteristics of the total vibration energy to change.